Biochemical Characterization of Aspergillus fumigatus AroH, a Putative Aromatic Amino Acid Aminotransferase - Dindo, Mirco; Costanzi, Egidia; Pieroni, Marco; Costantini, Claudio; Annunziato, Giannamaria; Bruno, Agostino; Keller, Nancy P.; Romani, Luigina; Zelante, Teresa; Cellini, Barbara (Frontiers in Molecular Biosciences, 2018)
The rise in the frequency of nosocomial infections is becoming a major problem for public health, in particular in immunocompromised patients. Aspergillus fumigatus is an opportunistic fungus normally present in the environment directly responsible for lethal invasive infections. Recent results suggest that the metabolic pathways related to amino acid metabolism can regulate the fungus-host interaction and that an important role is played by enzymes involved in the catabolism of L-tryptophan. In particular, in A. fumigatus L-tryptophan regulates Aro genes. Among them, AroH encodes a putative pyridoxal 5'-phosphate-dependent aminotransferase. Here we analyzed the biochemical features of recombinant purified AroH by spectroscopic and kinetic analyses corroborated by in silico studies. We found that the protein is dimeric and tightly binds the coenzyme forming a deprotonated internal aldimine in equilibrium with a protonated ketoenamine form. By setting up a new rapid assay method, we measured the kinetic parameters for the overall transamination of substrates and we demonstrated that AroH behaves as an aromatic amino acid aminotransferase, but also accepts L-kynurenine and α-aminoadipate as amino donors. Interestingly, computational approaches showed that the predicted overall fold and active site topology of the protein are similar to those of its yeast ortholog, albeit with some differences in the regions at the entrance of the active site, which could possibly influence substrate specificity. Should targeting fungal metabolic adaptation be of therapeutic value, the results of the present study may pave the way to the design of specific AroH modulators as potential novel agents at the host/fungus interface.